Enhanced GIRK2 channel signaling in Down syndrome: A feasible role in the development of abnormal nascent neural circuits - Kleschevnikov, Alexander M. (Frontiers in Genetics, 2022)
The most distinctive feature of Down syndrome (DS) is moderate to severe cognitive impairment. Genetic, molecular, and neuronal mechanisms of this complex DS phenotype are currently under intensive investigation. It is becoming increasingly clear that the abnormalities arise from a combination of initial changes caused by triplication of genes on human chromosome 21 (HSA21) and later compensatory adaptations affecting multiple brain systems. Consequently, relatively mild initial cognitive deficits become pronounced with age. This pattern of changes suggests that one approach to improving cognitive function in DS is to target the earliest critical changes, the prevention of which can change the ‘trajectory’ of the brain development and reduce the destructive effects of the secondary alterations. Here, we review the experimental data on the role of KCNJ6 in DS-specific brain abnormalities, focusing on the putative role of this gene in the development of abnormal neural circuits in the hippocampus of genetic mouse models of DS. It is suggested that the prevention of these early abnormalities with pharmacological or genetic means can ameliorate cognitive impairment in DS.